Hybrid Wireframe DNA Nanostructures with Scaffolded and Scaffold‐Free Modules. Issue 17 (12th March 2021) - Cui, Yan; Yan, Jun; Wei, Bryan
Abstract: The scaffolded DNA origami approach and the scaffold‐free LEGO approach both demonstrate an extraordinary self‐assembly capability for constructing all kinds of complex DNA nanostructures. Combining the construction elements of the two approaches, we introduce a hybrid framework to build wireframe structures in this study. A collection of two‐dimensional (2D) and three‐dimensional (3D) wireframe structures are presented to showcase the simple and versatile design. Our development reveals more of the ever‐expanding design space of structural DNA nanotechnology. Abstract : The integration of scaffold‐free modules to scaffolded DNA origami results in a hybrid architecture.